Changing Philosophies of Fisheries Management as Illustrated by the History of Fishing Regulations in Wyoming. Issue 1 (29th December 2015) - Rahel, Frank J.
Abstract : Inland fisheries management began in the United States in the 1800s with a focus on fish as food and the use of stocking to create new fisheries and replenish depleted stocks. In the early 20th century, recreational fishing came to the forefront and regulations limiting the number and size of fish that could be harvested were enacted. Major trends in the regulation of recreational fisheries included a reduction in creel limits, more complexity in the application of regulations, increasingly restrictive use of baitfish, and limitations on competitive fishing tournaments. In the latter part of the 20th century, fisheries managers embraced a broader perspective that included conservation of native species and control of invasive species. These changes in regulations reflect the evolution of fisheries management philosophy along pathways emphasizing fishing for sustenance, fishing for recreation, and, most recently, biodiversity management. This evolution is illustrated by the history of angling regulations in Wyoming.